Measurement of liquid film thickness in high energy gas-liquid two-phase flow / Zulfadzli Ridzuan - Zulfadzli , Ridzuan (2019)
Gas-liquid two-phase flow is common on industrial application especially in refrigeration system and power plant such as the nuclear power plant. The objective of this study was to measure the liquid film thickness and flow profile in high energy gas liquid two-phase flow. The experimental two-phase flow vertical channel rig was installed with Constant Current Electrical Method (CECM) sensors, data acquisition (DAQ) and a high-speed camera to capture flow pattern and the hold-up (liquid film thickness). Experimental data were recorded for wide range of flow condition with specific combination of velocities of both phases, gas and liquid. At higher gas superficial velocity, flow pattern is moving from bubbly to slug to churn flow to annular flow, while at higher liquid superficial velocity, bubbles formations were very stable. Film thickness was observed to decreased as higher gas superficial velocity was introduced, and up to certain level, annular flow can be observed. At higher slip ratio, the film thickness value is almost constant as the flow has established a fixed pattern.